﻿La primitiva decorazione pittorica del portico di S. Lorenzo fuori le mura : osservazioni sulla tecnica - Basile, Giuseppe (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1985)
The recent restoration of the earliest pictorial decoration of the portico of S. Lorenzo fuori le mura, executed under the author’s direction, provided the occasion for the reconsideration of a wide range of technical issues relating to the manufacture of the mediaeval frescoes there. Careful analysis of the technique used reveals new aspects of their making. The cycles, which date to the decade 1216-26 and the pontificate of Honorius iii, were restored according to one of the two preferred methods that were available and explanation is provided for this choice.